Silver entrepreneurship: A golden opportunity for ageing society - Bojanić Ivana Barković; Erceg Aleksandar; Sekuloska Jovanka Damoska (Economics and Business Review, 2024)
This paper aims to discuss the notion of silver entrepreneurship in the context of the silver economy. Policy-wise knowing who silver entrepreneurs are and what it takes to support them is an essential step to productively managing the ageing population and promoting an age-ready but age-friendly approach to creating a sustainable economy and society in the new demographic reality. The paper provides a theoretical and empirical literature review of silver entrepreneurship to identify the current state of the art. It also identifies selected policies and strategies aiming to foster silver entrepreneurship, representing a more inclusive and age-diverse entrepreneurial landscape. The silver entrepreneurship proves to be a challenging research field due to the elusive nature of entrepreneurship itself and the lack of universal definitions for this phenomenon.